How children think and learn : the social contexts cognitive development - Wood, David J. (Oxford, UK ; Malden, Mass : Blackwell, 1998)
Images of childhood and their reflection in teaching. A decade of development (maturation and learning). Are there stages of develoment? Learning how to think and learn. Language and learning.
Keywords: Psychology; Cognition in children; Learning, Psychology of; Cognition in children